The Risk of Acute Pancreatitis and Selective Serotonin Reuptake Inhibitors Use: A Meta-Analysis of Case-Control Studies - Shih-Wei Lai; Cheng-Chan Yu; Cheng-Li Lin; Kuan-Fu Liao (SAGE Publishing, 2020)
Background/Objective: Some case series and case report have shown the association between the risk of acute pancreatitis and use of selective serotonin reuptake inhibitors. The results of systematic studies were not consistent. Methods: A meta-analysis was performed to investigate the risk of acute pancreatitis associated with use of selective serotonin reuptake inhibitors. Results: There was no statistical association between the risk of acute pancreatitis and selective serotonin reuptake inhibitors use (odds ratio: 1.19, 95% confidence interval: 0.93-1.51). Conclusions: Despite reaching no statistical significance, the possibility of the association between the risk of acute pancreatitis and selective serotonin reuptake inhibitors use cannot be totally excluded.